Pengaruh Konsentrasi Pemlastis Pada Aplikasi Edible Coating Dari Tepung Pektin Apel Pada Buah Tomat - Naura Alfairuzy Quluby; Revani Triananda; Ayu Ratna Permanasari; Irwan Hidayatulloh; Fitria Yulistiani (Department of Chemical Engineering, Politeknik Negeri Bandung, 2022)
The edible coating is a protective layer that can regulate the rate of respiration. The purpose of the study is to see the effect of adding a plasticizer to the edible coating application of apple pectin flour on tomatoes. Edible coating was made with 2% apple pectin flour and plasticizers glycerol and sorbitol in concentrations of 0.5 percent, 0.6 percent, 0.7 percent, 0.8 percent, 0.9 percent, and 1 percent (v/v). Plasticizer concentrations of 1 percent glycerol and 0.7 percent sorbitol were found to be optimal. The addition of 1% glycerol resulted in 3.673 percent tomato fruit weight loss with a shelf life of more than 20 days, and the addition of 0.7 percent sorbitol resulted in 5.718 percent tomato fruit weight loss with a shelf life of more than 7 days. The percentage of elongation (2.47 percent and 1.125 percent), tensile strength (17.10 and 6.61 Mpa), water vapor transmission rate (5.955 and 7.070 g/m2/day), and thickness (0.06 mm) of edible coating with 1 percent glycerol and 0.7 percent sorbitol were obtained. The thickness, tensile strength, and water vapor transmission rate all met Japanese Industrial Standards, according to these results.